Overweight and obesity in children and adolescents: The South African problem - Hermanus Rossouw; Catharina Grant; Margaretha Viljoen (South African Journal of Science)
Overweight and obesity in children and adolescents are on the increase worldwide.Overweight and obesity increase the risk for the development of non-communicable diseases during childhood and adolescence, and predispose the individual to the development of overweight, obesity,ardiovascular disease, and metabolic and other disorders in adulthood.In Africa the number of overweight or obese children has doubled since 1990. In South Africa,overweight and obesity in children and adolescents are on the increase, but the prevalencevaries with age, gender and population group. These differences are important when intervention programmes and policies are considered. South Africa faces a double burden of disease where undernutrition and overweight or obesity are found in the same populations, in the same households and even in the same children. Malnutrition is a major contributor to the double burden of disease in South African children and adolescents.